2022
DOI: 10.3389/fvets.2022.757115
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of N6-Methyladenosine in Longissimus Dorsi Development in Yak

Abstract: N6-methyladenine (m6A) RNA undergoes epigenetic modification, which is the most extensive intermediate chemical modification in mRNA. Although this modification occurs in all living organisms, it is the most widely studied among mammals. However, to date, no study has investigated the m6A transcriptome-wide map of yak and its potential biological functions in muscle development. In this study, the differences of m6A methylation and gene expression in yak muscle development belonging to three age groups, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…In the work, association analysis showed that m6A modification abundance was negatively correlated with gene expression levels, which was consistent with two previous studies [ 51 , 52 ]. We also found that the expression of genes containing more than three m6A sites was much lower than that of genes containing one or two m6A sites, suggesting that m6A can regulate the degradation of mRNA [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the work, association analysis showed that m6A modification abundance was negatively correlated with gene expression levels, which was consistent with two previous studies [ 51 , 52 ]. We also found that the expression of genes containing more than three m6A sites was much lower than that of genes containing one or two m6A sites, suggesting that m6A can regulate the degradation of mRNA [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we identified numerous m 6 A methylation modification sites in both breast and leg tissues of Jingyuan chickens. These m 6 A peaks were primarily concentrated in the 3′UTR, CDS, and Stop codon regions, which aligns with findings from studies on Lexus rabbit and yak ( Luo et al, 2022 ; Ma et al, 2022 ). However, this pattern differed from the findings of Xu et al (2021) in their study on Ding'an goose, where m 6 A was primarily enriched in the CDS and start codon sequence, implying that the pattern of m 6 A modification could be species and tissue specific.…”
Section: Discussionsupporting
confidence: 85%
“…Given their slow growth rate and the low meat yield from yaks, there is a pressing need to expedite their growth in order to enhance meat production. In recent years, several research teams have investigated the transcriptional level mechanism of yak muscle development, providing fundamental insights for further exploration [ 6 , 14 , 37 ]. Building upon previous studies, we used the ATAC-seq and RNA-seq analysis methods for the first time to effectively identify the key factors influencing muscle development from a chromatin accessibility perspective, and explored the potential molecular mechanisms underlying the variations in skeletal muscle growth and development in the Tianzhu white yak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the substantial involvement of diverse myogenic regulators in skeletal muscle development, epigenetic modifications play a crucial role in facilitating muscle growth [ 8 , 12 , 13 ]. For instance, m6A modification intricately and negatively governs the expression levels of pivotal genes implicated in the growth and development of skeletal muscle in yaks [ 14 ]. The regulation of muscle growth and development is achieved through the methylation of gene promoters, which in turn controls the expression of genes associated with muscle function [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%